A Correlation between Communication Apprehension with the Participation of Tutorial Discussion on the Medical Student of Sebelas Maret University - Azka, Zalafi Kartika; Maryani, Maryani -; Putri, Anak Agung Alit Kirti Estuti Narendra (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: Problem Based Learning ( PBL ) has been used by Faculty of Medicine worldwide. Tutorial discussion was major activity at PBL, so student participation in tutorial discussion was important. Communication skills in tutorial discussion was very important and communication skills very affected by communication apprehension.Considering how important the communication skills in tutorial discussions and in effort to support participation in tutorial discussions, we interested to find the correlation between communication apprehension with the participation of tutorial discussion Methods: This research was an analytic observational study with cross sectional method. The subjects were medical student of Sebelas Maret University. The samples were selected by cluster sampling method, we got 75 respondent were from 9 tutorial group. Participation of the discussion was measured by direct observation and the communication apprehenssion was meassured by questionnaire. The data was analyzed by statistically method with Spearman Correllation Test. Result: The result of Spearman Correlation Test showed significant correlation with p = 0.000 (p<0.05), the strength of correlation was moderate, and had negative correlation (r = -0.566). Conclusion: There was negative correlation between the level of communication apprehension with participation of tutorial discussion. Keywords: communication apprehension, problem based learning, the activenness of tutorial discussion.